Validity and reliability assessment of the Persian version of the User Mobile Application Rating Scale. - Sheybak, Rezvaneh; Samouei, Rahele; Papi, Ahmad; Nouri, Rasool (Journal of Research in Medical Sciences, 2026)
Background: Smartphone health applications have gained popularity among users; however, the accuracy of the health information they provide often goes unchecked, potentially compromising user safety. This highlights the need for assessing mobile health applications. While several evaluation tools exist, including the User Mobile Application Rating Scale (uMARS), there is currently no available Persian version of uMARS. This study aims to validate the Persian version of uMARS. Materials and Methods: This cross-sectional study involved students from the management and medical information science, modern medical technologies, and rehabilitation science programs at Isfahan University of Medical Sciences. Participants were selected using cluster random sampling and nonrandom quota sampling, resulting in a total of 106 undergraduate, master's, and PhD students. Nonrandom quota sampling was then conducted among undergraduate, master's, and PhD students from the aforementioned schools. One hundred and six students were chosen using nonrandom quota sampling. First, this questionnaire was translated by two English-Persian language expert translators and backtranslated, and this was compared with the original uMARS. After assessing face and content validity, convergent and divergent validity were assessed. To determine reliability, the Cronbach's alpha method and test–retest was used. Results: Face, content, convergent, and divergent validity scale of uMARS was affirmed, and internal consistency for all subjective and objective quality dimensions with Cronbach's alpha of 0.929 was affirmed. The reliability of all subscale test–retest was also acceptable. Considering calculated indicators, the Persian version of uMARS in this study has a good reliability and validity and is expected to be useful for mobile health applications as a standard tool. Conclusion: uMARS Persian version is a reliable tool to assess the quality of mobile health applications from the user's perspective. This assessment framework offers a comprehensive evaluation of various aspects of mobile health applications, including their engagement, functionality, esthetics, information, and subjective quality.